Effect of Super-Chilling on the Shelf Life of Chicken Nuggets - Kanle, P.C.; Rathod, K.S.; Ambadkar, R.K. (Journal of Meat Science, 2018)
This study was conducted to assess the composition, physicochemical, microbiological and sensory quality of aerobically packaged  chicken nuggets stored at two different superchilling temperature (-2 ±0.5ºC and -0.5±0.5ºC) and compare with storage under frozen  (-20±1ºC) and chilling (4±1ºC) temperature for 35 days. The products stored at chilling (4±1ºC) temperature spoiled within 28 days.  The moisture content of super-chilled samples was significantly lower than frozen sample and higher than chilled samples. However  there was no significant variation in the fat content of the product stored at different temperatures. There was a significant increase in  pH of chilled samples than super-chilled with progress in the storage period. The TBA and tyrosine values of the superchilled samples  were significantly lower than chilled samples during the storage. Super-chilled nuggets showed significantly lower TPC and psychrophillic  counts as compared to chilled nuggets. Sensory evaluation also revealed significantly high scores for super-chilled product than chilled  nuggets indicating usefulness of super-chilling temperature for extension of shelf life.
Keywords: Aerobic Packaging; Chicken Nuggets; Quality analysis; Shelf Life; Super-chilling